Genome Mining Reveals Two Missing CrtP and AldH Enzymes in the C30 Carotenoid Biosynthesis Pathway in Planococcus faecalis AJ003T - Lee, Jun Ho; Kim, Jin Won; Lee, Pyung Cheon (Molecules, 2020)
Planococcus faecalis AJ003T produces glycosyl-4,4′-diaponeurosporen-4′-ol-4-oic acid as its main carotenoid. Five carotenoid pathway genes were presumed to be present in the genome of P. faecalis AJ003T; however, 4,4-diaponeurosporene oxidase (CrtP) was non-functional, and a gene encoding aldehyde dehydrogenase (AldH) was not identified. In the present study, a genome mining approach identified two missing enzymes, CrtP2 and AldH2454, in the glycosyl-4,4′-diaponeurosporen-4′-ol-4-oic acid biosynthetic pathway. Moreover, CrtP2 and AldH enzymes were functional in heterologous Escherichia coli and generated two carotenoid aldehydes (4,4′-diapolycopene-dial and 4,4′-diaponeurosporene-4-al) and two carotenoid carboxylic acids (4,4′-diaponeurosporenoic acid and 4,4′-diapolycopenoic acid). Furthermore, the genes encoding CrtP2 and AldH2454 were located at a distance the carotenoid gene cluster of P. faecalis.
Keywords: Aldehyde Dehydrogenase; Carotenoids; Databases, Protein; Genome, Bacterial; Metabolic Networks and Pathways; Oxidoreductases; Planococcaceae; carotenoids; genome mining; Planococcus faecalis